F(x)=2x+4/3
Replace f(x) by y:
y=2x+4/3
Solving for x:
y-4/3=2x+4/3-4/3
Subtracting the two terms on the left side of the equation:
(3y-4)/3=2x
Dividing both sides of the equation by 2:
[(3y-4)/3]/2=2x/2
[(3y-4)/3]*(1/2)=x
[(3y-4)*1]/[(3)*(2)]=x
(3y-4)/6=x
x=(3y-4)/6
Replace "x" by "f^(-1) (x)" (inverse function) and "y" by "x":
f^(-1) (x) = (3x-4)/6 Inverse function
Then, for x=6
f^(-1) (6) = [ 3(6)-4]/6
f^(-1) (6) = (18-4)/6
f^(-1) (6)= 14/6
f^(-1) (6) = 7/3
Her hair will have grown 6 after 7/3 = 2.33 months
Answer:
12.5
Step-by-step explanation:
put them in order from least to greatest: 11, 11, 12, 12, 12, 13, 13, 14, 15, 16
the middle is 12 and 13 so you do 12+13 then divide by 2
to get 12.5
hope this helps
Answer:
AAS
Step-by-step explanation:
x + 1
__________
3x+2 I 3x² +5x -3
3x² +2x
----------
3x -3
3x+2
--------
-5 is the remainder
Answer: −22w−25
Step-by-step explanation: Distribute:
=−22w+−5+5w+(−5)(w)+(−5)(4)
=−22w+−5+5w+−5w+−20
Combine Like Terms:
=−22w+−5+5w+−5w+−20
=(−22w+5w+−5w)+(−5+−20)
=−22w+−25